إبراز الجوانب البلاغية في قصائد المفتي جميل أحمد التهانوي: Highlights of the Rhetorical Devices in Jameel Ahmed Thanvi’s Poems - د. رابعة عمر حيات (Al Manhal Research Journal, 2022)
Mufti Jameel Ahmed Thanvi owes much of his fame and recognition to his association with Mufti Muhammad Ashraf Ali Tanvi. Not only did the former enjoy the privilege of being taught by the late Ashraf Ali Thanvi, but also had the honor of getting married to his daughter. He completed his early education from local religious institutions and strated teaching after graduation from Mazahir-Al-Uloom Madrassah. Owing to his academic efforts, which focused on Shari’ah and Arabic and Fiqh, Mufti Jameel gained command over Urdu, Persian and Arabic languages, and he attempted to compose poetry in all three. The purpose of his poetic works in Urdu and Persian were not to act an artistic outlet but to be an educational source of life’s experiences, and as far as his poems in Arabic are concerned, he wrote thirteen poems. Two of them were in tribute of Prophet Muhammad peace be upon him. Rest of the Arabic poems composed by Mufti Jameel Ahmed Thanvi were majorly elegies in honor of his own teachers and elders. Mufti’s rich Arabic vocabulary, command over grammar and rhetorical aspects are clearly reflected through his poems. This research will aim at highlighting the rhetorical devices used in his Arabic poems.